Perbandingan Akurasi dan Keberterimaan Terjemahan al-Rahīq al-Makhtūm antara Terjemahan Ahli dan Terjemahan Microsoft - Fauzaan, Farhan; Syihabuddin, Syihabuddin; Supriadi, Rinaldi; Murphy, Muhammad Ade (Study Program of Arabic Language Teaching, 2026)
This study measured the quality of MT translations of the text of Ar-Rahīq al-Makhtūm, a religiously nuanced historical work with a dense syntactic structure, and compared them with published scholarly translations. The approach used is qualitative, comparative, and descriptive. Data in the form of seven sentences of various fi'liyyah numbers were analyzed using the translation quality evaluation model from Nababan, including aspects of accuracy and acceptance. The assessment was carried out by expert respondents and native Indonesian speakers. The results showed that expert translations were superior in accuracy (score 40-31) and acceptability (40-32). The contribution of this research lies in the approach of naḥwu science in evaluation, which emphasizes the importance of the syntactic dimension in assessing the quality of machine translation of classical Arabic texts.